Chinas Belt and Road Initiative wandelt sich; China's Belt and Road Initiative is changing - Britta Kuhn (Wirtschaftsdienst, 2021)
Schon vor der Corona-Pandemie belasteten finanzielle und geopolitische Probleme die "Neue Seidenstraße": Chinas Gesamtinvestitionen gehen seit Jahren zurück, wichtige Bauprojekte sind unrentabel, die Partner in Ost- und Südosteuropa wenden sich ab, und umweltschädliche Vorhaben stoßen zunehmend auf Widerstand. Seit 2020 bieten wohlhabende Demokratien verstärkt Alternativen, und auch die Volksrepublik stundet Schulden. Xi Jinping forciert daher neben dem 'BRI Green Partnership' vor allem die "Digital Silk Road" und "China Standards 2035", also globale Technologie- und Normierungsprojekte. – – Even before the coronavirus pandemic, financial and geopolitical problems were weighing on the 'New Silk Road': China's overall investment has been declining for years, key construction projects are unprofitable, partners in Eastern and Southeastern Europe are turning away, and environmentally harmful projects are increasingly meeting resistance. Since 2020, affluent democracies reinforce alternatives and the People's Republic also defers debt. In addition to the "BRI Green Partnership", Xi Jinping is therefore pushing the "Digital Silk Road" and "China Standards 2035", i. e. global technology and standardisation projects.
Keywords: F21; O22; O53; 330; Neue Seidenstraße